G3 rohu dissemination dataset 2024 - Yeasin, Mohammed; Fakhruddin, Md.; Hamilton, Matthew (2025)
This dataset provides insights into the dissemination of the G3 Rohu strain in Bangladesh during 2024. It includes detailed information on spawn production and sales by hatchery partners, which serves as a basis for estimating the number of farmers adopting the G3 Rohu strain. This data aims to inform the reach of G3 Rohu adoption, facilitating evidence-based decision-making for future dissemination strategies.